Waves on Louisiana Continental Shelf Influenced by Atmospheric Fronts - Guo, Biyun (Sci Rep, 2020)
Ocean-atmospheric dynamical processes influence the wave characteristics, and sea surface temperature (SST). The processes that affect SST in the ocean area included surface heat fluxes, wind, and precipitation. In this study, we analyzed the wave data in response to the cold front passages over Louisiana continental shelf. The data examined in this research is mainly from WAVCIS (Wave-Current-surge Information System), Coastal Ocean Estuarine Dynamics Lab at Louisiana State University and Global Precipitation Climatology Project (GPCP). With respect to the wave response to the atmospheric forcing, here we consider: (1) the connection between wave variability and atmospheric frontal passages, and (2) the influence on the SST variations during the processes. The occurrences of wind wave, precipitation, and weather processes have distinct regularities. Atmospheric cold fronts have an important influence on wave formation and associated processes over Louisiana continental shelf.